One-pot Synthesis of Dihydropyrano[2,3-c]chromenes via a Three-component Reaction in Aqueous Media - Balalaie, Saeed; Khazaie, Ahmad; Ashouriha, Morteza (Combinatorial Chemistry & High Throughput Screening, 2013)
An efficient protocol for the synthesis of dihydropyrano [2,3-c] chromenes derivatives by one-pot threecomponent reaction of aromatic aldehydes, malononitrile or methyl cyanoacetate, and 4-hydroxy coumarin has been developed using catalytic amount (10%) of three different catalysts piperidine, triethyl amine, and natrium carbonate in aqueous media. The present protocol has significant features such as easy set-up and work-up, environmentally benign, high yields, short reaction times.
Keywords: 3-c]chromenes